A review of the East Palaearctic Pseudokiefferiella Zavřel, 1941 (Diptera: Chironomidae: Diamesinae), with description of new species and DNA barcoding of known species - Makarchenko, Eugenyi A.; Semenchenko, Alexander A. (Zootaxa, 2026)
Chironomids of the genus Pseudokiefferiella Zavřel from the East Palaearctic are revised using both morphological characters of adult males and molecular data. Four new species, P. inopinata sp. nov., P. kolchak sp. nov., P. krasheninnikovi sp. nov., and P. transarctica sp. nov. are described and figured. The adult males of P. matafonovi Makarchenko et Semenchenko and P. silinka Makarchenko et Semenchenko from the Amur River basin are briefly redescribed and annotated. A key to the known adult males of Pseudokiefferiella from the East Palaearctic is provided. The species delimitation, ASAP analysis, using COI DNA barcodes, assigned new species to unique mOTUs. Molecular data were also used for the reconstruction of the phylogenetic relationships within the genus Pseudokiefferiella.